2019
DOI: 10.1371/journal.pone.0218676
|View full text |Cite|
|
Sign up to set email alerts
|

The modulation of facial mimicry by attachment tendencies and their underlying affiliation motives in 3-year-olds: An EMG study

Abstract: From early in life, facial mimicry represents an important example of implicit non-verbal communication. Facial mimicry is conceived of as the automatic tendency to mimic another person’s facial expressions and is thought to serve as a social glue among interaction partners. Although in adults mimicry has been shown to be moderated by the social context and one’s needs to affiliate with others, evidence from behavioural mimicry studies suggest that 3-year-olds do not yet show sensitivity to social dynamics. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 79 publications
2
17
1
Order By: Relevance
“… Behavior 16 months, n = 48 * Southgate et al, 2009 Action observation Mu suppression starting before onset of observed movement. EEG 9 months, n = 15 * Stapel et al, 2010 Action observation Mu suppression stronger for extraordinary actions EEG 12 months, n = 12 * Tunçgenç et al, 2015 Synchrony 12 months-old but not 9 months old prefer social character (but not object(that have moved synchronously with them Behavior 9 months, n = 41; 12 months, n = 40 Upshaw et al, 2016 Action observation Mu suppression during observation related to grip strength EEG 12 months, n = 12 Vacaru et al, 2019 Mimicry (face) Spontaneous mimicry of face pictures. Effect of attachment style, not inhibitory control Behavior, EMG 3 months, n = 42 * Virji‐Babul et al, 2012 Action observation Mu suppression when watching videos of reaching, walking or object motion EEG 4−11 months, n = 14 * Warreyn et al, 2013 Action observation Mu suppression for object-directed and mimicked actions EEG 18−30, n = 17 * Yoo et al, 2015 Action observation Mu suppression during observation of grasp-with-tool actions.…”
Section: Scope Definitions and Why Study Interpersonal Motor Alignmementioning
confidence: 99%
“… Behavior 16 months, n = 48 * Southgate et al, 2009 Action observation Mu suppression starting before onset of observed movement. EEG 9 months, n = 15 * Stapel et al, 2010 Action observation Mu suppression stronger for extraordinary actions EEG 12 months, n = 12 * Tunçgenç et al, 2015 Synchrony 12 months-old but not 9 months old prefer social character (but not object(that have moved synchronously with them Behavior 9 months, n = 41; 12 months, n = 40 Upshaw et al, 2016 Action observation Mu suppression during observation related to grip strength EEG 12 months, n = 12 Vacaru et al, 2019 Mimicry (face) Spontaneous mimicry of face pictures. Effect of attachment style, not inhibitory control Behavior, EMG 3 months, n = 42 * Virji‐Babul et al, 2012 Action observation Mu suppression when watching videos of reaching, walking or object motion EEG 4−11 months, n = 14 * Warreyn et al, 2013 Action observation Mu suppression for object-directed and mimicked actions EEG 18−30, n = 17 * Yoo et al, 2015 Action observation Mu suppression during observation of grasp-with-tool actions.…”
Section: Scope Definitions and Why Study Interpersonal Motor Alignmementioning
confidence: 99%
“…According to discriminating power analyses, a cut-off score of 46 from the total scale distinguishes between securely (< 46) and insecurely attached (> 46) children [53,54]. Accordingly, 59% of children qualified as securely attached and 41% as insecurely attached, in line with previous findings on the prevalence rate of attachment security distribution in the general population [14,54,55]. Internal consistency analysis yielded a Cronbach's α of .735 for the avoidant subscale, .747 for the ambivalent/resistant subscale and .781 for the total scale, similar to previous results [34,43].…”
Section: Attachment Securitysupporting
confidence: 84%
“…Accordingly, some evidence indeed shows that early resistant attachment tendencies yield enhanced facial mimicry, suggesting higher intrinsic affiliation motivation, irrespective of the social context [14]. Another study found that adults with an avoidant attachment style tend to suppress facial mimicry responses to negative expressions (i.e.…”
Section: Individual Differences In the Motivation For Affiliationmentioning
confidence: 99%
“…Furthermore, recent evidence suggests that one's intrinsic motivation for affiliation modulates facial mimicry [14]. Facial mimicry of emotional expressions is not merely the result of activation matching, but is also influenced by one's affect.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, inner states and intrinsic characteristics (e.g. attachment orientation [14]; callous-unemotional traits [18], in concert with affiliation motives [19]; power motivation [20] modulate the extent to which individuals manifest facial mimicry in social contexts [21,22]).…”
Section: Introductionmentioning
confidence: 99%